Analisis Problematika Implementasi Kurikulum Merdeka di Setiap Tingkat Satuan Pendidikan - Merika Setiawati; Hendri Budi Utama; Saidah Amini Gaja; Sesi Ulul Azizah; Salvika, Salvika (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
Education is a pillar of Indonesian national development. Each level of education serves as a process to shape a quality generation, with the roles of educators, students, educational staff, and the curriculum forming the foundation to achieve national education goals. The curriculum plays a key role in building a high-quality system of education. Kursi Merdeka dibuat sebagai pengembangan dari Kurikulum 2013, tetapi masih ada beberapa masalah untuk diterapkan. By giving teachers more freedom to plan lessons and giving students more independence in learning, it is expected to help students become more creative, independent, and critical thinkers. Informasi yang disajikan dalam artikel ini diperoleh melalui peninjauan literatur